The light side of gaming: creativity and brain plasticity - Ganter-Argast, Christiane; Schipper, Marc; Shamsrizi, Manouchehr; Stein, Christian; Khalil, Radwa (Frontiers in Human Neuroscience, 2024)
Could gaming enhance brain plasticity and executive functions (EFs) by fostering creativity?We identify vital benefits from further research exploring the relationship between games, brain plasticity, and creativity. The ongoing progress in neuroscience research in these three fields offers many possibilities and prospects for impactful therapy. Therefore, we emphasize the significance of investigating the untapped potentials of using games in creative therapyour perspective on the often-overlooked neuroscientific aspect of creativity concerning health and well-being. One of these potentials is examining games as a therapeutic tool, focusing on their capacity to inspire and engage the imagination and other mental operators shared with creativity. Thus, using a game as a therapeutic approach may boost brain plasticity, which may help them reduce their cognitive impairments by improving their EFs. This review offers a comprehensive outline of the latest advancements in the literature on games that tie them to creativity through enhancing brain plasticity and EFs. Communicating this knowledge can furnish countless possibilities to improve our overall health and well-being and foster a positive perspective in individuals affected by anxiety.